Geophysical and Metalogenetic Modelling of the Copper Occurrence in Camaquã Sedimentary Basin, Brazilian Southern - Cortês, Ariane Raissa Pinheiro [UNESP]; Moreira, César Augusto [UNESP]; Paes, Renata Augusta Sampaio [UNESP]; Veloso, Dimitri Ilich Kerbauy [UNESP] (Springer Nature, 2019)
The geophysics application is indicated procedure in mineral exploration activities, by the quickness and possible global reduction of project cost. This work presents the results of the DC resistivity and induced polarization methods joint application, integrated to geological and structural data from a potentially mineralized area with copper sulfides, located in the Northern border of the Camaquã Sedimentary Basin, Brazil Southern. The mineral occurrence is characterized by malachite and azurite impregnation on silicified Neoproterozoic metarenite outcrop of Passo da Promessa Formation (Marica Group). The geophysics acquisition consists in six electrical tomography lines in Schlumberger arrangement with 440 m each, the lines were separated on two groups disposed at orthogonal form where the center area is located the mineral occurrence in surface. The results indicate a low resistivity and high chargeability zone 60 m deep, related to a sulfided zone and surrounded by elevated resistivity, which point silicification areas. The structural analysis has revealed two main fracture systems in the crystalline basement (NE–SW and NW–SE), one in the metarenite (NE-SW) and fold with a N20 axis. The 3D visualization model reveals that the mineralization is oriented in the N125 direction (NW–SE). The NW–SE fracture family is secondary but is present in the occurrence area and coincident with the relaxing direction of the folding event. This context corroborates with the hypothesis of filling NW–SE fractures, result which indicates the relevance of this preferential direction in future mineral research campaigns in the Camaquã Basin.
Keywords: 3D modelling; copper; DC resistivity; induced polarization; Mineral exploration